TELEMEDICINE IN FOCUS: ANALYSIS OF THE MOST COMMON ERRORS AND ETHICAL-LEGAL PARAMETERS - Almeida da Silva, Flaelma; Conti Boniares, Beatriz; Castro de Almeida, Diogo (Health and Society, 2025)
This article analyzes the advances and challenges of telemedicine in Brazil, recognized as a strategic tool for expanding access to healthcare, driven by technological progress and definitively regulated by the Federal Council of Medicine (CFM). The trajectory of national telehealth has been marked by significant transformations in the use of remote communication technologies, with its expansion accelerated during the COVID-19 pandemic. In this context, the emergency regulation of this practice culminated in the enactment of Law No. 14.510/2022, which provided legal support for remote medical care. The objective of this study is to identify the main errors that medical professionals must avoid in the practice of telemedicine, based on a critical analysis of scientific, normative, and doctrinal literature on the subject. To this end, a bibliographic review was conducted with emphasis on publications from the last five years, consulting the SciELO, Scopus, REASE, and LILACS databases. The investigation highlights the importance of professional civil liability, informed patient consent, and compliance with the General Data Protection Law (LGPD). As a result, it presents a synthesis of practices to be avoided and essential ethical-legal precautions for safe telemedicine practice. Thus, the study reinforces the potential of telemedicine as an instrument of health equity, provided it is used under appropriate technical, legal, and ethical standards.